Keterlibatan Ayah dalam Pengasuhan Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Fredericksen Victoranto Amseke (Institut Agama Kristen Negeri Manado, 2025)
Social emotional development is an important aspect that influences father's involvement in care in early childhood. The purpose of this study was to determine the effect of father's involvement in parenting on the social emotional development of children aged 5-6 years. The method in this study is quantitative. The sampling technique with purposive sampling is children aged 5-6 years. Respondents of this study amounted to 49 children aged 5-6 years at Betlehem Oesapa Barat Kindergarten, Kupang City. Data collection techniques in the form of a father's involvement scale in parenting and a social emotional development scale. The scale of father's involvement in parenting was developed by Hawkins et al, (2002) called Inventory of Father Involvement. The social emotional development scale was developed by Squires, Bricker and Twombly (2002) called the social emotional development scale. The data analysis technique was simple linear regression. The results of this finding found that father's involvement in parenting has a positive and significant effect on the social emotional development of children aged 5-6 years with a contribution of 98%, which means that the better the father's involvement in parenting can improve the social emotional development of early childhood. It is expected that fathers establish a safe and comfortable relationship with children, understand the needs and characteristics of children that can affect mental health in early childhood social emotional development.